Efficient and tunable Mn2+ sensitized luminescence via energy transfer of a novel red phosphor Ca19Mn2(PO4)14: Eu2+ for white LED. Issue 11 (1st June 2022) - Fan, Jiaqi; Zhou, Weiying; Luo, Jiabao; Zhang, Jilin; Wu, Zhan-chao; Dai, Xiaohua; Zhang, Xinguo
Abstract: The exploration of efficient and high-purity red phosphors is an urgent need in LED development. Due to the compact and compositional-tunable structure of whitlockite compound, manganese-based Ca19 Mn2 (PO4 )14 is chosen as phosphor host for Eu 2+ sensitization. Rietveld refinement, steady-state spectra, decay lifetime analysis and temperature-dependent emission spectra were investigated and clearly discussed. Under 360 nm excitation, Ca19 Mn2 (PO4 )14 : Eu 2+ shows a strong Mn 2+ sensitized emission at 655 nm with FWHM of 82 nm, benefiting from the short-distance-induced high-efficient Eu 2 -Mn 2+ energy transfer. Emission engineering of Ca19 Mn2 (PO4 )14 : Eu 2+ is achieved by Sr 2+ co-doping, leading to both tunable peak wavelength (ranging from 650 to 610 nm) and improved intensity (130% of original value). Moreover, Ca19 Mn2 (PO4 )14 : Eu 2+ exhibits a promising thermal stability where only 40% of emission intensity is lost at 200 °C. Finally, we explored the working performance of the fabricated RGB phosphor-converted white LED. The present work indicates that Ca19 Mn2 (PO4 )14 : Eu 2+ phosphor is of great potential as a promising and efficient red phosphor in phosphor-converted white LED.